2003
DOI: 10.1098/rspb.2003.2327
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying the impacts of exotic plant invasions

Abstract: Although the impacts of exotic plant invasions on community structure and ecosystem processes are well appreciated, the pathways or mechanisms that underlie these impacts are poorly understood. Better exploration of these processes is essential to understanding why exotic plants impact only certain systems, and why only some invaders have large impacts. Here, we review over 150 studies to evaluate the mechanisms underlying the impacts of exotic plant invasions on plant and animal community structure, nutrient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
1,171
2
26

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,437 publications
(1,255 citation statements)
references
References 69 publications
18
1,171
2
26
Order By: Relevance
“…Invasions have been recognized in a growing number of environments as being serious threats to the preservation of what we choose (by our choice of time scale) to be regarded as native fauna and flora [118][119][120]. Although the great majority of accidental introductions undoubtedly failed to become established, a substantial number became established, and some of these became serious pests [121].…”
Section: Invasiveness Of Gm Crops Into Natural Habitatsmentioning
confidence: 99%
See 1 more Smart Citation
“…Invasions have been recognized in a growing number of environments as being serious threats to the preservation of what we choose (by our choice of time scale) to be regarded as native fauna and flora [118][119][120]. Although the great majority of accidental introductions undoubtedly failed to become established, a substantial number became established, and some of these became serious pests [121].…”
Section: Invasiveness Of Gm Crops Into Natural Habitatsmentioning
confidence: 99%
“…They are only of minor importance globally with regard to invasive weed problems especially compared to other plant groups [129]. Globally, the feral plants that cause much of the economic damage are imported horticultural plants [118][119][120]. Unlike annual crops, these horticultural plants are mostly perennials that have extensive sexual and asexual reproduction.…”
Section: Conclusion On the Invasiveness Of Gm Crops Into Natural Habmentioning
confidence: 99%
“…It also became evident that the presence of invasive species can have a strong influence on the functioning of the invaded ecosystem (Levine et al, 2003;Vitousek, 1990), and in particular that in some cases invasive species change habitat conditions in a way that facilitate further invasions (Simberloff, 2006).…”
Section: The Classical Modelmentioning
confidence: 99%
“…Drake et al, 1989;Vitousek et al, 1987). However, only recently have frameworks for a more systematic research on impacts been suggested (Levine et al, 2003;Parker et al, 1999;Vitousek, 1990). Invasive species have been shown to substantially change ecosystem processes such as nutrient cycling, fire and other disturbances regimes, or hydrology (Levine et al, 2003;Mack et al, 2000).…”
Section: Biological Impact Researchmentioning
confidence: 99%
“…A recent crosscontinental comparison revealed that invasive plants significantly reduce native plant diversity in non-native habitats but not at home (Shah et al 2014). The invasive species can do so through many mechanisms (Levine et al, 2003), and the role of urbanisation-driven changes in ecological settings to influence such mechanisms is yet poorly understood.…”
Section: Introductionmentioning
confidence: 99%